A Century of Ecumenism as reflected in «Estudios Eclesiásticos» - Márquez Beunza, Carmen (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The ninety years’ commemoration of Estudios Eclesiásticos coincides with first centennial of ecumenical movement. During first decades, the magazine doesn’t pay too much attention to ecumenical questions. The Catholic Church’s opening to ecumenical movement during Pope John XXIII’s pontificate, bring a turn into the magazine’s trajectory, incorporating ecumenical issues. The postconciliar stage is characterized for the consolidation of this tendency.